Características reologicas y texturales de pasta de tomate (Solanum lycopersicum L.) comercializada en la ciudad de trujillo - 2019. - Mendoza Espinoza, Enma Darinka Inmaculada (2019)
The objective of this research was to determine the rheological and textural characteristics of three different brands of tomato pastes marketed in the city of Trujillo. The statistical design corresponded to one of a factor (trademark of tomato paste), with 3 replicas. First, compliance with the assumptions of normality and homogeneity of variances was evaluated, using the Anderson-Darling and modified Levene tests, respectively; When these were met, the parametric tests of the analysis of variance (ANOVA) were performed, and then, when there were significant differences (p <0.05), the Tukey multiple comparisons test was applied, which compared the results through the formation of subgroups and determined in this way the best treatment. All statistical tests were performed with a 95% confidence level. The R 3.2.5 and R 3.4.1 software was used to process the data, with the "agricolae" and "car" packages, respectively.